An analytical description of the force–deflection diagram of FRC. (February 2015) - Kovar, Martin; Foglar, Marek
Abstract: Fiber-reinforced concrete (FRC) has mechanical properties that enhance its suitability for use in structures subjected to high strain rates, e.g. blast or impact loading. The fracture energy value is the decisive material characteristic for assessing the damage to concrete structures due to loadings with high strain rates. This paper summarizes the results of tests focused on the fracture energy of fiber-reinforced concrete of various strength classes, fiber types and fiber contents, subjected to different loading rates. An analytical description of the force–deflection diagram of FRC can be a very efficient instrument for making a preliminary estimate of the fracture and mechanical properties of FRC. On the basis of our experiments and experiments from other authors, a tool for an analytical description of the force–deflection diagram for various strength classes, fiber types, etc. is proposed and evaluated.